Is the Surgical Approach Very Important to Treatment for Phyllodes Tumors? - Muhammet Fikri Kündeş; Kenan Çetin; Selçuk Kaya; Hasan Fehmi Küçük (Southern Clinics of Istanbul Eurasia, 2019)
INTRODUCTION[|]The aim of the present study was to evaluate the treatment modalities and recurrence status of patients diagnosed with phyllodes tumor in light of a literature search.[¤]METHODS[|]All female patients who received treatment for phyllodes tumor between January 2015 and January 2017 were included in our study. All data were collected through retrospective analysis. Histopathological results, type of surgery, application of chemoradiotherapy, tumor size, recurrence rate, and demographic data were analyzed.[¤]RESULTS[|]Twenty-five cases were evaluated. Of the 25 cases, 8 were diagnosed as malignant. The rest were 3 borderline and 14 benign and fibroadenomas. Three of 8 malignancies were treated with mastectomy, and the other 5 were treated with wide local excision. Recurrence occurred in two cases; one of them received chemotherapy, and the other had chemoradiotherapy. All 17 remaining patients underwent wide local excision. A single case was treated with mastectomy due to large tumor size.[¤]DISCUSSION AND CONCLUSION[|]There is still an ongoing debate for the treatment of phyllodes tumors. Negative margins for malignant cases play a major role for successful treatment. There is no consensus for the application of chemo- and radiotherapy.[¤]